IMPLEMENTASI PLATFORM MERDEKA MENGAJAR TERHADAP HASIL BELAJAR SISWA DI SMP NEGERI 16 GORONTALO - Madina, Abdul Haris; Rasid Yunus; Yuli Adhani (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to determine how the implementation of the Merdeka Mengajar Platform (PMM) affects student learning outcomes at SMP Negeri 16 Gorontalo, as well as to identify the challenges faced by teachers in utilizing the platform. This research employs a descriptive qualitative method. Data were collected through observation, interviews, and documentation. The findings indicate that although PMM offers various supporting features such as teaching materials, self-paced training, and diagnostic assessments, its utilization by teachers remains suboptimal. The main challenges include limited technological infrastructure, low digital literacy among teachers, and a lack of intensive training. As a result, the implementation of PMM has not had a significant impact on improving student learning outcomes. The study concludes that optimizing the use of PMM requires more targeted mentoring strategies, teacher capacity development, and strengthened infrastructure so that the platform can function effectively in supporting the Merdeka Curriculum.